2004
DOI: 10.1103/physrevlett.93.150501
|View full text |Cite
|
Sign up to set email alerts
|

Neutral Atom Quantum Register

Abstract: We demonstrate the realization of a quantum register using a string of single neutral atoms which are trapped in an optical dipole trap. The atoms are selectively and coherently manipulated in a magnetic field gradient using microwave radiation. Our addressing scheme operates with a high spatial resolution and qubit rotations on individual atoms are performed with 99 % contrast. In a final read-out operation we analyze each individual atomic state. Finally, we have measured the coherence time and identified th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
208
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 245 publications
(209 citation statements)
references
References 24 publications
1
208
0
Order By: Relevance
“…One possibility is to rely on spectroscopic addressability 84 enabled by spatially varying magnetic fields [85][86][87] or Stark shifts [88][89][90] . Another option is to rely on the nonlinearity of the atomic response to light and thus employ techniques such as STED 91 , spin-RESOLFT 92-94 , or dark-state-based techniques [95][96][97] .…”
Section: Applications To Exotic Quantum Magnetismmentioning
confidence: 99%
“…One possibility is to rely on spectroscopic addressability 84 enabled by spatially varying magnetic fields [85][86][87] or Stark shifts [88][89][90] . Another option is to rely on the nonlinearity of the atomic response to light and thus employ techniques such as STED 91 , spin-RESOLFT 92-94 , or dark-state-based techniques [95][96][97] .…”
Section: Applications To Exotic Quantum Magnetismmentioning
confidence: 99%
“…It has also been shown that APs can be used to robustly prepare superpositions of energy eigenstates [5]. Furthermore, it was proposed to prepare entanglement and implement quantum logic operations through adiabatic processes [6,7].We have recently demonstrated that a string of neutral Cs atoms stored in a standing wave optical dipole trap can be used to realize a quantum register [8]. There, quantum information was written into the two Cs hyperfine ground states by subjecting selected atoms to resonant microwave pulses.…”
mentioning
confidence: 99%
“…We have recently demonstrated that a string of neutral Cs atoms stored in a standing wave optical dipole trap can be used to realize a quantum register [8]. There, quantum information was written into the two Cs hyperfine ground states by subjecting selected atoms to resonant microwave pulses.…”
mentioning
confidence: 99%
See 2 more Smart Citations